Doskonalenie procesu produkcji z wykorzystaniem metody FTA w przedsiębiorstwie produkcyjno-usługowym = Improving the production process using the FTA method in a production and service enterprise - Mazur, Anna; Stachowiak, Agnieszka; Szymczak, Alicja; Witkowska, Patrycja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present the FTA error tree analysis. This method makes it possible to determine the causes of events and the probability of their occurrence and to indicate cause-and-effect relationships. This model allows you to graphically present connections between events and draw appropriate conclusions. On the example of a furniture manufacturer commissioned by a customer, a risk assessment was carried out using the FTA method. Through appropriate implementation and control of the effectiveness of the actions taken, new perspectives for the development of the company were presented.
Keywords: proces produkcji; metoda FTA; przedsiębiorstwo produkcyjno-usługowe; production process; FTA method; production and service company